Arguing with Aseneth: gentile access to Israel's living God in Jewish antiquity - Hicks-Keeton, Jill (Oxford University Press, 2018)
Arguing with Aseneth' shows how the ancient Jewish romance known as 'Joseph and Aseneth' moves a minor character in Genesis from obscurity to renown, weaving a new story whose main purpose was to intervene in ancient Jewish debates surrounding gentile access to Israel's God. Written in Greco-Roman Egypt around the turn of the era, 'Joseph and Aseneth' combines the genre of the ancient Greek novel with scriptural characters from the story of Joseph as it retells Israel's mythic past to negotiate communal boundaries in its own present. With attention to the ways in which Aseneth's tale "remixes" Genesis, wrestles with Deuteronomic theology, and adopts prophetic visions of the future, 'Arguing with Aseneth' demonstrates that this ancient novel inscribes into Israel's sacred narrative a precedent for gentile inclusion in the people belonging to Israel's God